(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the theoretical and methodological foundations of developing professional competence in future pedagogues based on a creative-pedagogical approach, the technological system of developing professional competence in future pedagogues based on a creative-pedagogical approach, and the effectiveness of developing professional competence in future pedagogues based on a creative-pedagogical approach. Also, components of professional competence development in future pedagogues based on the creative-pedagogical approach were analyzed.